Pelatihan Power Point Guna Meningkatkan Kreativitas dalam Membuat Media Pembelajaran Pondok Pesantren Darussalam - Irfanudin Irfanudin; Yudi Budi Yuniarso; Mansur Mansur; Zeni Sepia Ningsi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The rapid development of information technology requires educators to utilize digital learning media that are attractive, creative, and able to enhance students’ understanding. However, in many Islamic boarding schools (pesantren), the integration of technology into the teaching process is still limited, resulting in less innovative instructional delivery. This community service program was conducted to improve the competence of teachers and prospective teachers at Daarussalam Islamic Boarding School, Depok City, particularly in designing digital learning media using Microsoft PowerPoint. The training consisted of three stages: planning, implementation, and evaluation. During the implementation stage, participants were introduced to basic PowerPoint features, effective educational visual design techniques, and the integration of Islamic values into the media content. Evaluation was carried out through questionnaires and participant feedback to assess the effectiveness of the program. The results indicated that the training was highly successful, as participants were able to produce their own digital learning media and expressed increased creativity in delivering instructional materials. Thus, this training program has a positive impact on improving the quality of learning at the pesantren and is expected to support the continuous development of educators’ digital literacy.